Identifikasi Perilaku Pasangan Usia Subur Terhadap Keikutsertaan Program Keluarga Berencana Dengan Pendekatan Teori Perilaku Yang Terencanakan (Theory Of Planned Behaviour) - Anggie P Putri (Interest : Jurnal Ilmu Kesehatan, 2018)
Abstract: Attitude, Subjective Norm, Behaviour Control, Family Planning, Behaviour To Undergo Family Planning. This study aims to identify the influences of attitude, subjective norm, behaviour control and intention to attend Family Planning program using Theory of Planned Behaviour. The frame of this theory is tested to analize the influences of the constrution of this study, the understanding of attitude, subjective norm, behaviour control, intention to attend a program set by the government to controlling the population. Data collection was done by giving the questionnaire to 109 respondents who were undergoing Family Planning program in Jetiskarangpung, Sragen, Central Java Indonesia; but there are 100 valid questionnaires. The data is analized using T-test and then the variabels are analized using multiple Regression. The findings of this study shows that attitude (sig. 0,006), subjective norm (sig. 0,002), behaviour control (sig 0,012) gives significant influence of the intention to undergo the Family Planning program. This findings is aline with the philosphy within Theory of Planned Behaviour.